2020
DOI: 10.3389/fphar.2020.01339
|View full text |Cite
|
Sign up to set email alerts
|

Alantolactone Enhances the Phagocytic Properties of Human Macrophages and Modulates Their Proinflammatory Functions

Abstract: Aim of the Study: Phagocytosis is a crucial element of innate immune defense involved in bacterial killing. The aim of our study was to evaluate the influence of alantolactone on phagocytosis and cytokines release by THP1-derived macrophages. We assessed whether antimicrobial compound alantolactone (a sesquiterpene lactone present in Inula helenium L.) is able to stimulate immune functions of macrophages by increase of S. aureus uptake, phagosome acidification and further stimulation of phago-lysosomes formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Epithelial cells were pretreated with the G. squarrosa extract (at concentration range 25–100 μg/ml) or grindelic acid (at 10–50 μM) for 40 min at 37 °C, and then they were stimulated with LPS (1 μg/ml) for 20 min. The protein isolation was provided as we describe previously ( Gierlikowska et al, 2020b ). Cells were washed with ice-cold PBS, suspended in hypotonic buffer (5 mM NaF, 0.1 mM EDTA, 20 mM HEPES, 10 µM Na 2 MoO 4 ), and then centrifuged.…”
Section: Methodsmentioning
confidence: 99%
“…Epithelial cells were pretreated with the G. squarrosa extract (at concentration range 25–100 μg/ml) or grindelic acid (at 10–50 μM) for 40 min at 37 °C, and then they were stimulated with LPS (1 μg/ml) for 20 min. The protein isolation was provided as we describe previously ( Gierlikowska et al, 2020b ). Cells were washed with ice-cold PBS, suspended in hypotonic buffer (5 mM NaF, 0.1 mM EDTA, 20 mM HEPES, 10 µM Na 2 MoO 4 ), and then centrifuged.…”
Section: Methodsmentioning
confidence: 99%
“…These findings suggested that IAL—in combination with β-lactam antibiotics—may be a promising drug in the treatment of S. aureus pneumonia [ 183 , 184 ]. Furthermore, it could be shown that low micromolecular concentrations (1–20 µM) of ALT intensified the uptake of S. aureus and thus stimulated immune functions of macrophages [ 185 ]. However, IAL has also recently been found to exert strong synergistic effects with carbapenems (polymyxin B or colistin) in the treatment of mcr-1-positive Enterobacteriaceae such as K. pneumoniae and E. coli in vivo and in vitro [ 186 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…ALT and IAL have also been described as potential ailments for anti-inflammatory associated diseases by exerting immunomodulatory and anti-inflammatory effects via multiple pathways [ 185 , 193 , 194 ]. ALT increased phagocytosis, and simultaneously modulated cytokines production due to p65 NF-kB suppression [ 185 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike macrophages, maturation of neutrophilic phagosomes is dependent on fusion with preformed granules ( Nordenfelt and Tapper, 2011 ; Gierlikowska et al, 2020b ). Membrane proteins and granule contents are directed to distinct locations by precise trafficking and fusion/fission processes ( Nordenfelt and Tapper, 2011 ).…”
Section: To Phagocytose To Degranulate or To Make Extracellular Traps?mentioning
confidence: 99%